Representation of school library and librarian stereotype in Indonesia film Mariposa - Nina Mayesti; Syifa Salsabila Putri (Library and Archive, Universitas Gadjah Mada, 2026)
Introduction. School libraries and librarians’ images and stereotypes in various media have largely remained unchanged over time. This image can affect the use of the school library. This study aims to identify and explain the representation of school libraries and librarians, alongside the stereotypes of school librarians in one of Indonesia's popular films, Mariposa. Research Methods. Scenes were selected for observation and documentation to collect data on verbal and nonverbal element.. Data Analysis. The data were analyzed using Peirce’s triadic semiotic model, consisting of sign, object, and interpretant components which provides a systematic framework for elaborating how social perception and professional stereotypes are formed through representation. Results. The school library was depicted as a place where characters interacted and developed relationships. It also became a place for students to study independently and in groups. In addition to conducting duties as information professionals, school librarians play a supporting role in the students’ social relations as library patrons. Stereotypes persist aroundto school librarians focusing on appearance and professionalism. Mariposa films feature positive and negative depictions of school library and librarians. Conclusion. School library representation is depicted in positive light, while the portrayal of school librarian remains partly confined and persistent to the longstanding traditional stereotypes.